Atlas of Challenges and Opportunities in European Neighbourhoods - Beckouche, Pierre; Besnard, Pierre; Pecout, Hugues (Springer Nature, 2016)
Human Geography; World Regional Geography (Continents, Countries, Regions); Political Science; Economic Geography